2012
DOI: 10.1007/s12070-012-0584-8
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Post-Tonsillectomy Secondary Haemorrhage Following Coblation Tonsillectomy

Abstract: To examine the incidence of haemorrhage following tonsillectomy, to explore the usefulness of antibiotic in preventing postoperative haemorrhage and to examine if the haemorrhage depended on the level of expertise of the surgeon. A retrospective review analysing tonsillectomy method, the rate secondary haemorrhage, the grade of operating surgeon. A v 2 analysis was used to determine the statistical difference between the haemorrhage rates of different tonsillectomy methods. One thousand three hundred and thirt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…No significant difference was found between the three groups regarding postoperative early or late bleeding (Ozkiris et al, 2013). In the retrospective study by Praveen et al (2013) on 1,336 tonsillectomy patients, postoperative hemorrhage incidence was found to increase in coblation patients following tonsillectomy with coblation, cold technique, helica thermal and bipolar cautery. In a study by Chimona et al (2008) on pediatric age group, perioperative bleeding was higher in the group treated with cold dissection when compared to cold technique radiofrequency and thermal welding tonsillectomy.…”
Section: Discussionmentioning
confidence: 92%
“…No significant difference was found between the three groups regarding postoperative early or late bleeding (Ozkiris et al, 2013). In the retrospective study by Praveen et al (2013) on 1,336 tonsillectomy patients, postoperative hemorrhage incidence was found to increase in coblation patients following tonsillectomy with coblation, cold technique, helica thermal and bipolar cautery. In a study by Chimona et al (2008) on pediatric age group, perioperative bleeding was higher in the group treated with cold dissection when compared to cold technique radiofrequency and thermal welding tonsillectomy.…”
Section: Discussionmentioning
confidence: 92%
“…Controversy still persists in the world literature regarding the occurrence of significantly increased bleeding rates after hot tonsillectomy methods. Some studies have compared post-operative haemorrhage among electrocautery or coblation tonsillectomy patients versus cold dissection patients, and found significant increase in the first [18,[21][22][23]. However, other studies reported no significant differences [14], and concern was expressed that the number of well designed, large, randomised, controlled trials was insufficient to detect small differences in secondary haemorrhage rates [13].…”
Section: Discussionmentioning
confidence: 99%
“…Praveen et al reported 6.3% return to theatre for Coblation method and overall secondary hemorrhage for Coblation was 12.9% 10 . In our study, only 1.09% of patients return to theatre was recorded.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, post-tonsillectomy bleeding incidence was 3.8%. Praveen et al reported 9.3% readmission with secondary hemorrhage 10 . Clark et al reported a rate of 1.5% after Coblation method, all patients were managed conservatively 11 .…”
Section: Discussionmentioning
confidence: 99%